Non Hodgkin Lymphoma Among Children: Pathological Aspects and Diagnostic Challenges - Sabrine Derqaoui; Ismail Boujida; Oussama Marbouh; Lamiaa Rouas; Laila Hessissen; Najat Lamalmi (SAGE Publishing, 2022)
Non-Hodgkin lymphoma (NHL) are common malignancies in children. Available data on clinico-pathological aspects of pediatric NHL in developping countries are limited and diagnostic approach appears more delicate with absence of molecular studies. The objectives of our study are: analyzing the pathological spectrum of NHL among children and highlighting challenges in the diagnosis including: limited biopsic material; unususal subtyptes, age group, or localization. We retrospectively analyzed clinico pathological characteristics of 101 NHL's cases among children diagnosed in the Pediatric's pathology unit over a period of 4 years There were 78 (77.2%) male and 23 (22.8%) female. The median age was 7.2 years. The most common histologic subtypes of NHL were Burkitt lymphoma in 65 patients (64.4% ); followed by lymphoblastic lymphoma in 22 patients, large B-cell lymphoma in 9 patients ( 8.9%); anaplastic T cell lymphoma in 3 patients; NOS mature T cell lymphoma and pediatric type follicular lympoma in 1 patient each. In conclusion, this study Morocco illustrates the pattern of distribution of NHL and emphasizes challenges in the diagnosis of these neoplasms.